Output Volatility and Exchange Rate Considerations Under Inflation Targeting : A Review - Petreski, Marjan (International Journal of Economics and Financial Issues, 2012)
The objective of the paper is to offer a critique on the theoretical and empirical literature on inflation targeting (IT). It seems to exist a consensus in the theoretical literature that this monetary regime reduces both inflation and output volatility, mainly through building monetary policy credibility. When the role of the exchange rate is discussed, while there are some arguments that, as an instrument, it should not be explicitly stated in the central-bank loss function, theoretical arguments and evidence are still mixed as regards the effectiveness of exchange-rate management under IT. On the empirical front, the paper concludes that despite the fact that the work on IT in the last two decades has been immense in quality and quantity, still there is no quantitatively-credible study for the developing world, let alone a study that appropriately measures the regime switch from one monetary strategy to another. Keywords: Inflation targeting; Output volatility; Exchange rate; Trade-off; DSGE JEL Classifications: E42; E52; E58